Mental Health, Substance Abuse, and Suicide Among Homeless Adults. Issue 4 (4th July 2017) - Lee, Kyoung Hag; Jun, Jung Sim; Kim, Yi Jin; Roh, Soonhee; Moon, Sung Seek; Bukonda, Ngoyi; Hines, Lisa
ABSTRACT: This study explored the role of mental health and substance abuse problems on the suicidal ideation and suicide attempts of 156 homeless adults. The logistic regression results indicated that homeless adults with anxiety were significantly more likely than those without anxiety to have both suicidal ideation and suicide attempts. Also, homeless adults with drug abuse were significantly more likely than those without drug abuse to have suicidal ideation. The study suggests that to reduce the suicide of the homeless, case managers need to screen mental health and substance abuse issues and to provide appropriate treatment services at homeless shelters.